Oral isotretinoin versus acitretin in the treatment of plantar warts in adults - Ahmad A.E. Nofal; Samar M. Najah; Ahmed S.A. ElShafy (Journal of the Egyptian Women’s Dermatologic Society)
Background Plantar warts are benign epithelial tumors that are forced inward due to pressure on the toes or sole of the foot and may become very painful if not treated. Many treatment options are available including topical treatments, lasers, and immunotherapy. However, data about systemic therapies are lacking. Objective To compare the efficacy and safety of acitretin versus oral isotretinoin in the treatment of multiple plantar warts. Patients and methods This randomized comparative double-blinded study included 80 adult patients with multiple plantar warts. The cases were divided into two groups: acitretin group (40 cases with a dose of 0.5 mg/kg/day) and isotretinoin group (40 cases with a dose of 0.5 mg/kg/day). The reduction in wart size and photographic comparisons at the beginning and every 2 weeks for 3 months were used to assess the treatment efficacy in the two groups. After therapy ended, a follow-up was conducted every month for 6 months to observe any recurrence. Results Complete response was observed in 30%, partial response in 55%, and no response in 15% of patients of acitretin group while complete response was achieved in 15%, partial response in 45%, and no response in 40% of patients of isotretinoin group with statistically significant difference in favor of acitretin (P=0.03). Compared with acitretin, oral isotretinoin was associated with a shorter duration to a complete response (83.3% of cases achieved complete response in <2 months compared with only 16.7% in acitretin group) (P=0.006). Conclusion Acitretin is superior to oral isotretinoin as a therapeutic option for plantar warts, but both are effective and safe. Since they are resistant to other traditional therapy techniques, they can be seen as valuable therapeutic choices for multiple plantar warts.